ANALISIS KESALAHAN MENERAPKAN BAHASA SQL (STRUCTURE QUERY LANGUAGE) MATA KULIAH BASIS DATA - Rachmawati Rachmawati (Program Studi Pendidikan Matematika, 2019)
Query is instruction deeping to access data in data basis. SQL is lingual one be utilized to get communication or gets interaction among user with database. SQL merupakanBahasa that popular dalammemanajemen data basis. This research intent to describe type and cause of IKIP'S college student fault Utomo's Kindness in apply SQL'S instruction (Query Language's structure) on Basis college eye Data. Observational method that is utilized in this research constitutes descriptive kualitatif. Data collecting instrument in observational it covers: (1) essay as case study those are utilized to know kesalahanmahasiswa's position in designs ERD. (2 ) interviews to college student those are utilized to get causal factor data glosses over. Base faults observational result in apply SQL'S instruction that done by IKIP'S college student Utomo's Kindness Baleful amongst those is conceptual fault for case study 1 as much 30% and case studies 2 as much 33%. Case study technical foul 1 no, meanwhile case study 2 as much 0,25%.